NEDA-3 status including cortical lesions in the comparative evaluation of natalizumab versus fingolimod efficacy in multiple sclerosis. (October 2018) - Puthenparampil, Marco; Cazzola, Chiara; Zywicki, Sofia; Federle, Lisa; Stropparo, Erica; Anglani, Mariagiulia; Rinaldi, Francesca; Perini, Paola; Gallo, Paolo
Background: Cortical lesions (CLs) are typical of multiple sclerosis (MS) and have been recently incorporated in MS diagnostic criteria. Thus, the 'no evidence of disease activity' (NEDA) definition should now include CLs. The aim of this study was to evaluate the NEDA3 + CL status in natalizumab- or fingolimod-treated relapsing remitting MS (RMS) patients. Methods: Natalizumab- or fingolimod-treated RMS patients were enrolled in a 2-year longitudinal study based on clinical and magnetic resonance imaging (MRI) evaluations performed respectively biannually and annually. CLs were detected by double inversion recovery. The NEDA3 + CL condition was evaluated at baseline (T0) and at the end of the first (T1) and second (T2) year. Results: Of the 137 RMS patients included in the study, 86 were propensity-matched. At T2, the annualized relapse rate was lower on natalizumab ( p = 0.021), but the effect on white matter lesions ( p = 0.29) and the proportion of NEDA-3 patients ( p = 0.14) were similar in the two treatment arms. At T2, 11.6% natalizumab- and 62.8% fingolimod-treated patients had new CLs ( p < 0.001) and a higher proportion of natalizumab-treated patients (55.8% versus 11.6%, p < 0.001) achieved the NEDA3 + CL status (hazard ratio 5.2, p < 0.001). Conclusion: The incorporation of CLs in the NEDA-3 definition highlighted the higher efficacy of natalizumab versus fingolimod in suppressing disease activity in RMS patients.